2013
DOI: 10.1091/mbc.e12-04-0300
|View full text |Cite
|
Sign up to set email alerts
|

SmgGDS antagonizes BPGAP1-induced Ras/ERK activation and neuritogenesis in PC12 cell differentiation

Abstract: BPGAP1 controls morphogenesis, migration, and ERK signaling by the concerted action of its multiple domains. Its BCH domain targets K-Ras and induces robust ERK activation and neuronal differentiation in a process antagonized by SmgGDS. The results highlight unique cross-talk of two regulators of GTPases in Ras/ERK signaling and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…NGFβ binds to two different receptors: the TrkA tyrosine kinase receptor with high affinity and the p75 NTR with low affinity [32]. In PC12 cells, NGFβ activates the ERK signal through the TrkA, that leading to neurite outgrowth [33]. In the present study, we confirmed the NGFβ activities, whereas SPARC alone did not change the phosphorylated state of ERK1/2 and subsequent neuritogenesis.…”
Section: Discussionsupporting
confidence: 75%
“…NGFβ binds to two different receptors: the TrkA tyrosine kinase receptor with high affinity and the p75 NTR with low affinity [32]. In PC12 cells, NGFβ activates the ERK signal through the TrkA, that leading to neurite outgrowth [33]. In the present study, we confirmed the NGFβ activities, whereas SPARC alone did not change the phosphorylated state of ERK1/2 and subsequent neuritogenesis.…”
Section: Discussionsupporting
confidence: 75%
“…An interesting protein in this context is SmgGDS, which associates with the active and inactive forms of Rac1 , being sequestered in the nucleus together with Rac1 . Its function in neurons appears to be related to neurite outgrowth in physiological conditions . Rac1 function is also very well controlled as for example by TIAM‐1 and Trio, two GEFs able to activate Rac1 .…”
Section: Introductionmentioning
confidence: 99%
“…We recently established the roles of the BCH domain in modulating a variety of cellular events ( Pan and Low, 2012 ; Ravichandran and Low, 2013 ). Of interest, these BCH domain–containing proteins display distinct subcellular localizations.…”
Section: Discussionmentioning
confidence: 99%